CD301b+ macrophage: the new booster for activating bone regeneration in periodontitis treatment - Can Wang; Qin Zhao; Chen Chen; Jiaojiao Li; Jing Zhang; Shuyuan Qu; Hua Tang; Hao Zeng; Yufeng Zhang (Nature Publishing Group, 2023)
Abstract Periodontal bone regeneration is a major challenge in the treatment of periodontitis. Currently the main obstacle is the difficulty of restoring the regenerative vitality of periodontal osteoblast lineages suppressed by inflammation, via conventional treatment. CD301b+ macrophages were recently identified as a subpopulation that is characteristic of a regenerative environment, but their role in periodontal bone repair has not been reported. The current study indicates that CD301b+ macrophages may be a constituent component of periodontal bone repair, and that they are devoted to bone formation in the resolving phase of periodontitis. Transcriptome sequencing suggested that CD301b+ macrophages could positively regulate osteogenesis-related processes. In vitro, CD301b+ macrophages could be induced by interleukin 4 (IL-4) unless proinflammatory cytokines such as interleukin 1β (IL-1β) and tumor necrosis factor α (TNF-α) were present. Mechanistically, CD301b+ macrophages promoted osteoblast differentiation via insulin-like growth factor 1 (IGF-1)/thymoma viral proto-oncogene 1 (Akt)/mammalian target of rapamycin (mTOR) signaling. An osteogenic inducible nano-capsule (OINC) consisting of a gold nanocage loaded with IL-4 as the "core" and mouse neutrophil membrane as the "shell" was designed. When injected into periodontal tissue, OINCs first absorbed proinflammatory cytokines in inflamed periodontal tissue, then released IL-4 controlled by far-red irradiation. These events collectively promoted CD301b+ macrophage enrichment, which further boosted periodontal bone regeneration. The current study highlights the osteoinductive role of CD301b+ macrophages, and suggests a CD301b+ macrophage-targeted induction strategy based on biomimetic nano-capsules for improved therapeutic efficacy, which may also provide a potential therapeutic target and strategy for other inflammatory bone diseases.